2020
DOI: 10.2147/rmhp.s265992
|View full text |Cite
|
Sign up to set email alerts
|

<p>COVID-19 in Shanghai: IPC Policy Exploration in Support of Work Resumption Through System Dynamics Modeling</p>

Abstract: Purpose: It is unclear how and to what extent various infection prevention and control (IPC) policies affect the spread of an epidemic during work resumption. In order to assess the impact of IPC policies, this research addresses the results of a policy simulation in Shanghai, China, which estimates the transmission dynamics of COVID-19 under various IPC policies and offers evidence-based outcomes of work resumption policies for the world. Materials and Methods: This simulation research is based on a system dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…This study shows that if the authorities in Wuhan could have identified and quarantined more than 60% of the close contacts of infected persons, they could have allowed the city to re-open sooner. Previous studies have shown that on average, 80% of close contacts can be traced and quarantined in many regions in China [ 9 , 28 ]. However, track-and-trace measures also have capacity issues.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that if the authorities in Wuhan could have identified and quarantined more than 60% of the close contacts of infected persons, they could have allowed the city to re-open sooner. Previous studies have shown that on average, 80% of close contacts can be traced and quarantined in many regions in China [ 9 , 28 ]. However, track-and-trace measures also have capacity issues.…”
Section: Discussionmentioning
confidence: 99%
“…SD models were well recognized and practiced in research in developing and evaluating national health policy [ 54 , 65 69 ] and investigating complexity and uncertainties in healthcare and health-related socioeconomic systems [ 55 , 62 , 70 75 ]. In the past two years, scholars have extensively used SD models to understand the transmission dynamics, impacts of containment measures, and prediction of COVID-19 spread [ 76 87 ].…”
Section: Introductionmentioning
confidence: 99%
“…The parameter settings were in line with previous literature ( 19 21 ), and the detailed information is presented in Appendix 1 .…”
Section: Methodsmentioning
confidence: 99%